Hypocrite in a pouffy white dress : tales of growing up groovy and clueless - Gilman, Susan Jane. (New York : Warner Books, 2005)
Summary : Chronicles growing up in Manhattan in the 1970s, where the author goes through many changes, being in turn a young ballet dancer in a Puerto Rican neighborhood, a rock music fan, a cub reporter, and a feminist.
Keywords: Gilman, Susan Jane; Girls -- New York (State) -- New York -- Biography; Young women -- New York (State) -- New York -- Biography; New York (N.Y.) -- Biography; Geneva (Switzerland) -- Biography